Energy Efficiency of the Ukrainan Economy: Problems and Prospects - LUNOVAТ. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
The purpose of the article is to assess the current state of energy efficiency of Ukrainian economy and outline ways to increase it. The problem of high energy intensity of Ukrainian GDP is studied. The Ukraine’s position in the world on this indicator is analyzed. It is established that the main reasons for low energy efficiency of the national economy are the depreciation of fixed assets of large industrial enterprises; technological losses of electricity in the networks, which account for 11.6% of the total supply; lack of financial resources for the implementation of energy efficiency measures, lack of a systematic approach to energy consumption. The experience of implementation of Smart Grid projects of intellectual energy in the countries of the world is considered. It is established that more than 2930 organizations from 50 countries of the world take part in these projects. The main investments in Smart Grid projects are concentrated in: Denmark, Germany, Spain, France, Great Britain, France, Belgium and Sweden. In the European Union, companies implementing such innovative projects are reimbursed half of the costs of their implementation. The directions of the state energy saving policy in Ukraine are described: adoption of the Law of Ukraine “On Energy Saving”; creation of the State Agency for Energy Efficiency and Energy Saving of Ukraine; approval of the Energy Strategy of Ukraine for the period up to 2035; development of the draft Concept of integrated implementation of Smart Grid in Ukraine until 2035, which aims to reduce technological losses of electricity to 7.5%. It is concluded that it is necessary to create energy management systems (SEM) at large enterprises, which will optimize the volume and modes of electricity consumption and reduce its losses in the production process. The main functions of SEM, principles of energy efficiency management at the enterprise and functions of the energy manager are defined.